Dentistry and HIV: University professors' role in establishing a basis for judgment - Garbin, Clea Adas Saliba [UNESP] (2007)
The aim of this study was to determine whether there are differences in the attitudes of Dentistry School Professors from two universities, one private and one public concerning HIV-positive patients or HIV-positive health care professionals. A questionnaire Was handled to all profession at the Araçatuba Dental School of São Paulo State University - FOA-UNESP (public) and Lins Dental School of the Piracicaba Methodist University - FOL-UNIMEP (private). When asked if they would be willing to be treated by an HIV-infected health care professional, 38.9% of the 77 professors at FOA-UNESP replied that they would accept only non-invasive treatments and 13% would not accept any kind of treatment; the same applied to 42.4% and 15.2% of the 33 FOL-UNIMEP professors. Among the 54 professors at FOA-UNESP and 27 at FOL-UNIMEP providing clinical service, only 31.5% and 18.5% stated that they treat HIV-infected persons like any other patient. The results were very similar in both schools. Although they reported that they taught their students not to act in a discriminatory manner towards HIV-positive patient the professors themselves showed prejudice towards infected patients and professionals. Consequently, this topic trust be further debated in the academic milieu.